Visualizing the perturbation of cellular cyclic di-GMP levels in bacterial cells - Ho, Chun Loong (2013)
Cyclic di-GMP (c-di-GMP) has emerged as a prominent intracellular messenger that coordinates biofilm formation and pathogenicity in many bacterial species. Developing genetically encoded biosensors for c-di-GMP will help us understand how bacterial cells respond to environmental changes via the modulation of cellular c-di-GMP levels. Here we report the design of two genetically encoded c-di-GMP fluorescent biosensors with complementary dynamic ranges. By using the biosensors, we found that several compounds known to promote biofilm dispersal trigger a decline in c-di-GMP levels in Escherichia coli cells. In contrast, cellular c-di-GMP levels were elevated when the bacterial cells were treated with subinhibitory concentrations of biofilm-promoting antibiotics. The biosensors also revealed that E. coli cells engulfed by macrophages exhibit lower c-di-GMP levels, most likely as a response to the enormous pressures of survival during phagocytosis.